Do you know this syndrome? Hand-foot syndrome - Cintia Santos Braghiroli; Rodrigo Ieiri; Juliana Polizel Ocanha; Rafael Bispo Paschoalini; Hélio Amante Miot (Sociedade Brasileira de Dermatologia, 2017)
ABSTRACT Hand-foot syndrome is a common cutaneous adverse effect associated with certain systemic chemotherapy drugs. It is characterized by erythema, edema, and burning sensation, especially over palmoplantar surfaces. We report the case of an elderly patient undergoing chemotherapy after a breast cancer surgery who developed symptoms two months after the start of the regimen. There are no studies that explore specific therapies. Suggestive therapy include reducing agent dosage, increasing the interval between cycles, or even stopping chemotherapy. Emollients, analgesics, and cold packs are described as effective. After alopecia and mucositis, hand-foot syndrome is the most common adverse dermatologic reaction to chemotherapeutic agents.